Innovation science: between models and machines. Issue 2 (3rd May 2016) - Juhl, Joakim
ABSTRACT: Academic scientists are increasingly required to acquire industry funding, which affects the scope and purpose of their research. In Denmark, Mode 2 inflected ideas have turned universities' research toward industrial application where the fabrication of 'robust knowledge' is tied to commercial innovation. By analyzing the representative modeling of theoretical physicists that aided the implementation of new control solutions, this paper investigates how Mode 2 challenged traditional disciplinary boundaries between engineering and physics. The paper thus presents a case of non-engineers' move toward 'engineering' from outside the disciplinary boundary of engineering. The physicists' preference for theoretical rigor resulted in models that despite not being validated with production data were useful to the factory. Questions are raised about the challenges that the physicists' normative baggage entailed when they engaged in commercial application. The case signifies how Mode 2 inspired neoliberal science policy constitutes a new competitive market for the application of science and illuminate how theoretical physics was translated into a service for commercial innovation. In the process, physics, the identities of the physicists, the factory and its process control converged around shared success criteria and thus formed a new domain of work that I conceptualize as innovation science . The case demonstrates some of the demarcation challenges associated with the political reframing of science and the work it takes for science and non-science to develop beneficiary relationships, which translate into new challenges and potential applications for engineering.